Original articleCytochrome C oxidase activity and nitric oxide synthase in the rat brain following aluminium intracerebral application - Stevanović, Ivana D.; Jovanović, Marina D.; Čolić, Miodrag; Ninković, Milica; Jelenković, Ankica; Mihajlović, Rosa (Folia Neuropathologica, 2013)
In the present study we investigated the cytochrome C oxidase (CO) activity and nitric oxide synthase (NOS) isoenzyme expression after intrahippocampal AlCl3 application in selective vulnerable brain structures. A single dose of AlCl3 was applied in the CA1 sector of rats hippocampus. For biochemical analysis, the animals were killed 10 min and three days after the treatment and forebrain cortex, basal forebrain and hippocampus were removed. Activity of CO was decreased bilaterally in the AlCl3-treated groups in all examined brain structures. We also applied immunohistochemical techniques to identify changes induced by AlCl3 injection after survival periods of 10 min and three days. Both the nNOS and eNOS stains were detected in the hippocampus of controls and AlCl3-treated animals, but iNOS labelling was present in the hippocampus only three days after AlCl3 application. An increased iNOS expression three days post AlCl3 administration could be involved in the mechanism of CO activity depletion.